(untitled) (International Journal of Food and Nutritional Sciences, 2024)
The customer will use this web-based application system.This website is intended for employers who do fieldwork. The registration request will be issued to the manager when the employee registers for the account with his data.The employee may only access his account by logging in when the administrator approves his registration request. The employee’s GPS coordinates will be collected when he logs into his account. The employee’s presence inside the designated office radius will be ascertained by cross-referencing these GPS coordinates with the office coordinates.The employee may only log out of his account after the designated working hours. Additionally, the procedure of authenticating the employee and office location will be repeated every five minutes after the employee logs in to his account. An admin will receive a notice if an employee logs in and then leaves the workplace. An administrator can access an employee’s data by using their employee username. He may see the list of workers who have left the office during business hours as well as the login and logout information.Since the employee’s GPS position is tracked, he won’t try to add any proxy attendance. The administrator’s job is to approve or disapprove registration requests from new hires.